Synthesis and tunable photoresponse for core-shell structured NaGdF4:Yb, Er@SiO2@Eu(TTA)3Phen nanocomplexes. (15th July 2018) - Li, Yao; Jiao, Jiqing; Yan, Peipei; Liu, Lihua; Wang, Jiuxing; Wang, Yao; Huang, Linjun; Liu, Jixian; Belfiore, Laurence A.; Tang, Jianguo
Abstract: Highly monodispersed core-shell structured NaGdF4 :Yb, Er@SiO2 @Eu(TTA)3 Phen(2-Thenoyltrifluoroacetone (TTA), 1, 10-Phenanthroline monohydrate (Phen)) nanospheres were synthesized via two-step process. These nanospheres with diameter of 13 nm were encapsulated in SiO2 shell via micro-emulsion preparation. The ligand-sensitized Eu complexes attached to the outer surface of SiO2 . The green (542 nm) and red (610 nm) light were excited by NIR and UV illumination, respectively. Thus, tunable photoresponse was possible in the core-shell structured hybrid nanocomposites. Under upconversion process, 5-fold increase at 542 nm and a 14-fold increase at 660 nm could be achieved under 980 nm laser, respectively. Graphical abstract: Unlabelled Image